EFFECTS OF ALCOHOL CONSUMPTION ON SERUM LIPIDOME - THE CARDIOVASCULAR RISK IN YOUNG FINNS STUDY - Kosonen, Roosa (My University, 2024)
There is an association between alcohol consumption and clinical lipid markers but lipidomidome-wide connections are currently unclear. Aim of this study was to study cross-sectional association of alcohol consumption with serum lipidome in a population cohort of 1969 men and women aged 30-45 years. The study subjects were participants of the Cardiovascular Risk in Young Finns Study. The Cardiovascular Risk in Young Finns Study is an on-going follow-up study of atherosclerosis precursors of Finnish children and adolescents. The first cross-sectional survey was conducted in 1980, when 3596 participants, were randomly chosen in each university hospital area in Finland from the national population register. 2204 of these individuals were re-examined in 2007, then aged 30-45 years. Individuals with type 2 diabetes, subjects with missing risk factor data and outliers of glucose and daily amount of drinks were excluded from the present analyses. Therefore, the present study cohort included 1969 subjects. Serum lipidome analysed by using liquid chromatography-tandem mass spectrometry. The statistical tests were performed with Statistical Analysis System version 9.4. Multiple testing corrections were performed using the Bonferroni method. After Bonferroni correction alcohol intake was found to be significantly associated with concentrations of 195 out of 437 metabolites, after adjusting age and sex. Acylcarnitines, ceramides, phosphatidylethanolamines, phosphatidylglycerols, phosphatidylinositols and triacylglycerols were positively correlating with alcohol consumption. Previous studies have reported similar results but nothing in this scale. More research taking into account additional confounding factors are needed to clarify whether some of these lipids could be used as potential biomarkers for alcohol risk use.
Keywords: alkoholi, lipidomiikka